Implementation of Religious Moderation in the Development of Micro, Small and Medium Enterprises (MSMEs) - Erwin; Muh. Abdi Imam; Irna; Haifa Syukur; Aqifha Putri Ramadhani (Prodi Sosiologi Agama, 2025)
In the era of globalization, Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic growth and job creation. However, MSMEs often face challenges in the form of intense competition and unethical business practices. This study aims to explore the contribution of religious moderation to MSME development through a qualitative approach with a case study method. The concept of religious moderation is understood as an effort to balance religious values with sustainable and responsible business practices. Data were obtained through in-depth interviews and participant observations of MSME actors who integrated the principles of moderation in their business activities. The results of the study indicate that religious moderation encourages the formation of reflective business ethics, inclusive cooperative relationships, and social orientation in business decision making. These findings indicate that religious moderation has a practical role in encouraging more ethical business practices and oriented towards social sustainability. Thus, religious moderation not only functions as a theological concept, but also as a value framework that can enrich the practice and orientation of MSME development amidst contemporary economic challenges.